Toxocara canis infection: Unusual trigger of systemic lupus erythematosus. Issue 4 (6th July 2015) - Levy, Michaël; Bourrat, Emmanuelle; Baudouin, Véronique; Guillem, Colette; Peuchmaur, Michel; Deschênes, Georges; Fila, Marc
Abstract Infection by Toxocara canis can cause systemic vasculitis. We report here a unique case of systemic lupus erythematosus (SLE) triggered by T. canis infection. An 8‐year‐old girl was treated with albendazole therapy for common toxocariasis, but she developed two weeks later, asthenia, fever, infiltrated maculopapular eruption of the face, peripheral vascular disease with necrosis of the fingers and inflammatory anemia with proteinuria. Anti‐nuclear, anti‐DNA and anti‐Sm antibodies positivity, together with minimal change nephritis with mesangial exclusive IgM deposit on renal biopsy and clinical relapse after initially successful steroid therapy, led to the diagnosis of SLE. T. canis infection can trigger systemic lupus but must also be ruled out of the differential diagnosis given its association with autoimmunity.